150 YEARS ON CANCER CHALLENGING: WHAT DOES IT MEAN, WHERE ARE WE? - Fernando Raphael de Almeida Ferry; Marilza Campos de Magalhães; Rogerio Neves Motta; Patrícia Canelha Ribeiro-Alves; Maria Helena Roustand Rabay Vermot-Petit-Outhenin; Carlos Alberto Morais de Sá (Revista de Pesquisa Cuidado é Fundamental Online)
Abstract: Introduction: Cancer comes from Latin language where it means crab. Onco comes from Greek language meaning mass, bulk or tumor. Tumors are classified on biological features as low-grade, intermediate or high-grade malignancy according to tumor cell differentiation. There have been about three hundred thousands of new cancer cases reported per year in Brazil. Tumorigenesis mechanisms, complexity and conflicts: Cancer has been considered a genetic disease caused by mutations in genes governing cell growth or chromosomal events as amplifications, deletions, inversions or translocations. Single nucleotide polymorphisms (SNPs) have been considered associated with cancer. It has been identified 1.42 million polymorphisms in the human genome. Epigenetic gene modulation may be a key mechanism in cancer development and metastasis. Chromatin-histone complex may be modified by phosphorylation, acetylation, methylation and/or ADP-ribosylation. MicroRNAs may be incorporated in mRNA targets and influence several biological processes as development, differentiation and apoptosis. Apoptosis is a way cells undergo programm deaths by activation of extrinsic cell surface death-mediating receptor, activation of mitochondrial mediated intrinsic pathway or non-apoptotic forms of cell death. In cancer there seems be failure, loss or absence of forms of cell death and overactivation of kinase growth factor receptors. Treatment and Prevention: Surgery is the better method to cure patients with solid tumors confined to local disease. Ionizing radiation may be administered as an isolated local form of cure, but also to extend limits of a treated region. Prevention depends on educational strategies, chemopreventive agents or early diagnosis for solid tumors. Advanced forms of cancer presentation are rarely cured and depend on combination of surgery, irradiation, chemotherapy and biological agents. Conclusion: At 150 years on cancer challenging, we do not know what it does really mean, nor even cure, effective treatment or prevention has been achieved. Descriptors: Cancer a non solved problem. Tumorigenesis complex and conflicts mechanisms. Cancer treatment and prevention.